2014
DOI: 10.1002/crat.201400076
|View full text |Cite
|
Sign up to set email alerts
|

Double Br sources fabrication and photocatalytic property of p‐n junction BiOBr/ZnO composites for phenol removal

Abstract: P-n junction BiOBr/ZnO composites were prepared by a facile solvothermal process with double Br sources of CTAB and KBr. The samples were characterized by XRD, XPS, SEM, TEM, HRTEM, DRS, BET and PL. The BiOBr/ZnO composites exhibited much higher photocatalytic activity than single BiOBr and ZnO for the degradation of phenol under simulated sunlight irradiation. The enhanced photocatalytic activity of BiOBr/ZnO composites could be mainly ascribed to the high-efficiency separation of photogenerated electron-hole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Such outstanding effi ciency of the BiOX-15 nanosheets is also remarkably higher than the values of recently reported Bi-based photocatalysts (Table S1, Supporting Information), such as Bi 4 Ti 3 O 12 /BiOI, [ 13 ] BiOI/ZnSn(OH) 6 , [ 15 ] BiOI/BiPO 4 , [ 32 ] BiOI/Bi 2 O 3 , [ 33 ] and BiOBr/ZnO. [ 34 ] To further illustrate the photo catalytic reaction, pseudo-fi rst-order kinetics were fi tted from the degradation process, where the value of the rate constant value k was equal to the corresponding slope of the fi tting line as displayed in Figure 2 b. The rate constant value for BiOX-15 sample is 0.0263 min −1 , which is much higher than those of BiOX-18 (0.0206 min −1 ), BiOX-9 (0.0118 min −1 ), BiOX (0.0053 min −1 ), Bi (0.0064 min −1 ), and P25 (0.0006 min −1 ) samples, also showing the superior photocatalytic activity of the BiOX-15 sample.…”
Section: Photocatalytic Activity and The Mechanism Of Biox Nanosheetsmentioning
confidence: 78%
“…Such outstanding effi ciency of the BiOX-15 nanosheets is also remarkably higher than the values of recently reported Bi-based photocatalysts (Table S1, Supporting Information), such as Bi 4 Ti 3 O 12 /BiOI, [ 13 ] BiOI/ZnSn(OH) 6 , [ 15 ] BiOI/BiPO 4 , [ 32 ] BiOI/Bi 2 O 3 , [ 33 ] and BiOBr/ZnO. [ 34 ] To further illustrate the photo catalytic reaction, pseudo-fi rst-order kinetics were fi tted from the degradation process, where the value of the rate constant value k was equal to the corresponding slope of the fi tting line as displayed in Figure 2 b. The rate constant value for BiOX-15 sample is 0.0263 min −1 , which is much higher than those of BiOX-18 (0.0206 min −1 ), BiOX-9 (0.0118 min −1 ), BiOX (0.0053 min −1 ), Bi (0.0064 min −1 ), and P25 (0.0006 min −1 ) samples, also showing the superior photocatalytic activity of the BiOX-15 sample.…”
Section: Photocatalytic Activity and The Mechanism Of Biox Nanosheetsmentioning
confidence: 78%
“…It has been reported that the CB , VB of p-type BiOBr and n-type ZnO were 0.8 eV, 0.85 eV and 3.5 eV, 3.9 eV, respectively, which has been depicted in Figure 11 [11]. The type of band alignments at the semiconductor interface is attributed to type II staggered alignment [9].…”
Section: Mechanism Of the Enhancement Effectmentioning
confidence: 88%
“…The facile hydrothermal method was applied in the synthesis of BiOBr-ZnO composites. Compared with the only reported solvothermal method using CTAB as the solvent in [10], the operating procedures for the hydrothermal method were much easier and more environmentally friendly and showed a higher yield and purity [11]. To our knowledge, this is the first time in which the hydrothermal method was used to fabricate the BiOBr-ZnO heterojunction.…”
Section: Introductionmentioning
confidence: 99%
“…Coupling semiconductor photocatalysts with matched band energy levels has been proven to be an effective strategy for facilitating efficient photogenerated charge separation [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Owing to its desirable band gap (2.7 eV) and peculiar layered structure constituted by interlacing [Bi 2 O 2 ] slabs with double bromine slabs, BiOBr is emerging as a relatively efficient and stable visible-light-activated photocatalyst.…”
Section: Introductionmentioning
confidence: 99%